Preparing the future post-mortem analysis of beryllium-based JET and ITER samples by multi-wavelengths Raman spectroscopy on implanted Be, and co-deposited Be. (5th June 2017) - Rusu, M.I.; Pardanaud, C.; Ferro, Y.; Giacometti, G.; Martin, C.; Addab, Y.; Roubin, P.; Minissale, M.; Ferri, L.; Virot, F.; Barrachin, M.; Lungu, C.P.; et al.
Abstract: This study demonstrates that Raman microscopy is a suitable technique for future post mortem analyses of JET and ITER plasma facing components. We focus here on laboratory deposited and bombarded samples of beryllium and beryllium carbides and start to build a reference spectral databases for fusion relevant beryllium-based materials . We identified the beryllium phonon density of states, its second harmonic and E 2G and B 2G second harmonic and combination modes for defective beryllium in the spectral range 300–700 and 700–1300 cm −1, lying close to Be–D modes of beryllium hydrides. We also identified beryllium carbide signature, Be2 C, combining Raman microscopy and DFT calculation . We have shown that, depending on the optical constants of the material probed, in depth sensitivity at the nanometer scale can be performed using different wavelengths . This way, we demonstrate that multi-wavelength Raman microscopy is sensitive to in-depth stress caused by ion implantation (down to ≈30 nm under the surface for Be) and Be/C concentration (down to 400 nm or more under the surface for Be+C), which is a main contribution of this work. The depth resolution reached can then be adapted for studying the supersaturated surface layer found on tokamak deposits.